2000
DOI: 10.1067/mva.2000.107565
|View full text |Cite
|
Sign up to set email alerts
|

The Pruitt-Inahara shunt maintains mean middle cerebral artery velocities within 10% of preoperative values during carotid endarterectomy

Abstract: The Pruitt-Inahara shunt is able to maintain adequate middle cerebral artery velocity in 98% of patients undergoing carotid endarterectomy. Alterations in blood pressure can significantly affect flow through the shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…The Pruitt-Inahara shunt is unable to maintain an adequate blood flow at the level of the ipsilateral middle cerebral artery in 2% of patients. 11 Sundt et al 1 reported a 0.5% incidence of neurologic complications due to shunt-related microembolization caused by the embolization of atheromatous material from the plaque before performing the CEA or with the passage of embolic material through the shunt, termed snowplow embolism. Loftus et al 6 described a case of distal ICA dissection due to the insertion of a shunt.…”
Section: Discussionmentioning
confidence: 99%
“…The Pruitt-Inahara shunt is unable to maintain an adequate blood flow at the level of the ipsilateral middle cerebral artery in 2% of patients. 11 Sundt et al 1 reported a 0.5% incidence of neurologic complications due to shunt-related microembolization caused by the embolization of atheromatous material from the plaque before performing the CEA or with the passage of embolic material through the shunt, termed snowplow embolism. Loftus et al 6 described a case of distal ICA dissection due to the insertion of a shunt.…”
Section: Discussionmentioning
confidence: 99%
“…The Pruitt Inahara Shunt is a device that allows for the maintenance of cerebral blood flow during carotid surgery. This shunt is placed into the vessel and uses balloons to keep the artery patent as the plaque is being removed [9]. Since the PA in our case was located distal to the vascular patch site or the endarterectomized area of the carotid artery, we concluded that the balloon portion of the shunt likely caused blunt trauma to the artery.…”
Section: Discussionmentioning
confidence: 93%
“…1). [18][19][20][21] The clamping time for the CCA for inserting the PI shunt is never more than 2 minutes. As irreversible hypoxic-ischemic brain injury begins after 5 minutes, this maneuver is considered safe.…”
Section: Discussionmentioning
confidence: 99%